2021
DOI: 10.1007/s12072-021-10181-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes for acute-on-chronic liver failure in COVID-19: a large multi-center observational cohort study

Abstract: Objective Coronavirus disease 2019 [COVID-19] infection in patients with chronic liver disease [CLD] may precipitate acute-on-chronic liver failure [ACLF]. In a large multi-center cohort of COVID-19-infected patients, we aim to analyze (1) the outcomes of patients with underlying CLD [with and without cirrhosis] and (2) the development and impact of ACLF on in-hospital mortality. Design We identified 192 adults with CLD from among 10,859 patients with confirmed COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Drug-induced liver damage is a plausible addictive factor to the observed liver blood marker abnormalities after the beginning of therapy [ 33 ]. Furthermore, as recently reported, COVID-19 in patients with chronic liver disease (CLD) may precipitate acute-on-chronic liver failure (ACLF) [ 36 ]: in-hospital mortality was similar between patients with CLD with or without cirrhosis but was higher in those with cirrhosis who developed ACLF, with a trend for increased mortality by grade of ACLF [ 36 ].…”
Section: Sars-cov-2 Infection and Multiorgan Damagementioning
confidence: 99%
“…Drug-induced liver damage is a plausible addictive factor to the observed liver blood marker abnormalities after the beginning of therapy [ 33 ]. Furthermore, as recently reported, COVID-19 in patients with chronic liver disease (CLD) may precipitate acute-on-chronic liver failure (ACLF) [ 36 ]: in-hospital mortality was similar between patients with CLD with or without cirrhosis but was higher in those with cirrhosis who developed ACLF, with a trend for increased mortality by grade of ACLF [ 36 ].…”
Section: Sars-cov-2 Infection and Multiorgan Damagementioning
confidence: 99%
“…Furthermore, another study about risk factors and outcomes for acute-on-chronic liver failure in COVID-19 across multi-center studies in the United States also indicated that the presence of chronic liver disease or cirrhosis by itself is not associated with a difference in in-hospital mortality after comparison with an age, sex, and comorbiditymatched control using propensity control methods [4]. Therefore, mechanical ventilation and day-30 mortality should be fairly compared by balancing the baseline characteristics between patients with and without chronic liver disease.…”
Section: To the Editormentioning
confidence: 99%
“…However, mortality was not different when comparing CLD patients with or without cirrhosis. Moreover, mortality was similar between the CLD cohort and matched control without CLD [ 216 ].…”
Section: Gastrointestinal Involvement In Covid-19mentioning
confidence: 99%